2010
DOI: 10.1377/hlthaff.2009.0629
|View full text |Cite
|
Sign up to set email alerts
|

The Revolving Door Of Rehospitalization From Skilled Nursing Facilities

Abstract: Medicare policymakers have recently become interested in changing the payment incentives around rehospitalizations. Using merged claims data, our analyses indicate 23.5% of Medicare beneficiaries discharged from the hospital to a skilled nursing facility (SNF) were directly readmitted within 30 days at a cost to Medicare of $4.34 billion in 2006. Although these results indicate significant potential savings, we also found that SNF rehospitalizations were heterogeneous in nature and varied considerably across l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
423
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 428 publications
(433 citation statements)
references
References 12 publications
6
423
3
1
Order By: Relevance
“…Hospitalizations are common in this population; in 2006, 23.5% of the people admitted to a post-acutecare skilled-nursing facility were rehospitalized within 30 days. 1 Several studies suggest that many of these hospitalizations are inappropriate, avoidable, or related to conditions that could be treated outside the hospital setting -and they cost more than $4 billion per year. 1-3 Avoidable hospitalizations are also common among long-stay residents of nursing homes (see graphs).…”
mentioning
confidence: 99%
“…Hospitalizations are common in this population; in 2006, 23.5% of the people admitted to a post-acutecare skilled-nursing facility were rehospitalized within 30 days. 1 Several studies suggest that many of these hospitalizations are inappropriate, avoidable, or related to conditions that could be treated outside the hospital setting -and they cost more than $4 billion per year. 1-3 Avoidable hospitalizations are also common among long-stay residents of nursing homes (see graphs).…”
mentioning
confidence: 99%
“…Functional decline, considered as geriatric syndrome, should be a particular focus for SNF clinicians to reduce the "revolving door" effect (transfers to and from the hospital). 4 These efforts could help to reduce Medicare-related financial burdens. Two studies about reducing the "revolving door" effect suggest the promising role of applying intensive rehabilitation therapy in functionally declining seniors in both acute hospital and post-acute care settings.…”
Section: Discussionmentioning
confidence: 99%
“…2 Reports show that one-fourth of SNF residents will return to the hospital within 30 days, 3 with an estimated cost of $14.3 billion in 2011. 4 That financial burden is then compounded by the added expenditure of transferring residents from SNF to the hospital. In total, 40% of hospital transfers from SNFs may be either unnecessary or avoidable, meaning that the resident could have been cared for safely at a lower level of care and at lower cost.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Readmissions from nursing home facilities to acute care hospitals are a critical health care issue, impacting both quality and safety for nursing home residents. Mor, et al [6] reported that in 2006 almost 25% of nursing home residents were readmitted to an acute care facility within 30 days of nursing home admission, at a cost of $4.34 billion. A more recent study conducted in 2011 by the Department of Health and Human Services reported similar readmission rates among Medicare nursing home residents, but found that the costs had tripled to $14.3 billion.…”
Section: Introductionmentioning
confidence: 99%